تاريخ وحضارة مدينة سدراتة الأثرية بالجنوب الشرقي الجزائري – نموذج للمدينة الإسلامية- - بن صغير حضري, يمينة (مجلة الواحات للبحوث والدراسات, 2024)
يزخر المغرب الإسلامي بنماذج لمدن كان لها دور تاريخي وحضاري، اختلفت أسباب وجودها وعوامل تطورها كالقيروان، وبجاية، وتلمسان، ومراكش، وفاس ....وغيرها، وتعد مدينة سدراتة بالجنوب الشرقي الجزائري نموذجا للمدن الإسلامية التي اختلفت عن النمط المعماري الصحراوي المعروف بالقصور، فجاءت كجوهرة في وسط الرمال، إذ اعتبرت العاصمة الإباضية الثانية بعد سقوط الدولة الرستمية 296ه /909 م بتيهرت، فبعد عطاء دام أكثر من ثلاثة قرون خربت هده المدينة على يد ابن غانية الميورقي سنة 426 / 1236، فهجرها السكان وغطتها الرمال بمرور الزمن، وقد لفتت هذه المدينة أنظار الباحثين الغربيين أثناء الاستعمار الفرنسي فأجريت بها العديد من الحفريات الأثرية على يد كل من الباحث لارجو ، وهارولد تاردي ، وبول بلانشي، وفوشي ، و أخرها حفرية مارغريت فان برشم ، والتي كان من نتائجها العثور على بعض معالم المدينة، والعديد من البقايا الأثرية المتنوعة خاصة القطع الجصية المزخرفة، التي نقل العديد منها إلى متاحف فرنسا، كما وضع جزء منها بالمتحف الوطني للفنون الإسلامية بالجزائر العاصمة، وبالرغم من محاولة بعض الباحثين الجزائريين في السنوات الأخيرة لإجراء بعض الحفريات والبحوث أكاديمية إلا أن أكثرها لم ينشر، والمدينة اليوم تغطيها الرمال كليا، لا يعرفها الجزائريون إلا من خلال المؤرخين. The Islamic Maghreb is full of exemplary of cities that had a historical and cultural role. The reason for their existence and the factors of their development are different, such as Kairaoiane, Bejaia, Tlemcen, Marrakech, Fes … The city of Sedrata in the south east of Algeria is considered as a model of the Islamic cities which differ from the desert architectural style known as Kesour(palaces). It appears as a diamond in the middle of sand. Sedrata was considered the second Ibadi capital after the fall of the state of Rustamid 296 / 909, in Tiaret. After more than three centuries, Sedrata was destroyed by Ibn Ghania Elmaiorgy in 296 / 909. Tts inhabitants abandoned it then it was covered by sand over time. During the French colonialism, Sedrata attracted the attention of Western researchers; many archaeological excavations were conducted by Largeau, Arold Tardy, Paul Blanchet, Faucher and Margierte. The last of which was conducted by Van Berchem who managed to discover some landmarks of the city, many various archaeological remains, especially decorative plaster pieces, many of which were transferred to museums of France. A part of these archaeological was also placed in the national museum of Muslim Art in Algiers- Algeria. Although some Algerian researchers have tried recently to conduct some excavations and carry out some academic research, but most of them havn’t been published. Today, the city is completely covered in sand and the Algerians only know it through Historians.
Keywords: Archéologie – Sedrata

Cyrille Aillet, Patrice Cressier, Sophie Gilotte (éd.), Sedrata. Histoire et archéologie d’un carrefour du Sahara médiéval à la lumière des archives inédites de Marguerite van Berchem: Madrid, Casa de Velázquez (« Collection de la Casa de Velázquez », 161), 2017, 497 p. - Mesnil, Emmanuelle Tixier du (Médiévales, 2020)
Keywords: Archéologie – Sedrata; Recension

Sedrata-Sijilmassa : exemple inédit de circulations artistiques au Sahara médiéval - Capel, Chloé (Vivre, circuler et échanger sur la bordure septentrionale du Sahara (Antiquité-époque moderne), 2020)
Keywords: Archéologie – Sedrata